Pelaksanaan Program Penanggulangan Tuberkulosis Berdasarkan Peraturan Daerah - Nafilla, Nur; Yuniarti; Teguh Irawan; Wahyuningsih (Jurnal Kesmas Asclepius, 2025)
The purpose of this study was to implement a TB control program at the Wiradesa Community Health Center based on Pekalongan Regency Regulation No. 5 of 2018. The study used a descriptive qualitative method with the CIPP (Context, Input, Process, Product) evaluation model approach. Data collection techniques were through in-depth interviews and documentation. The results showed that the Context aspect was in accordance with regulations, but still faced challenges of social stigma and an unsupportive environment. In the Input aspect, trained human resources and adequate facilities were available, but limited cadres, employee rotation, limited funds, and a lack of modern detection tools were obstacles. The Process aspect showed data-based and cross-sectoral planning, but its implementation was hampered by the workload of officers, low patient awareness, and geographical constraints. Monitoring was carried out routinely every 3 months despite a lack of supervisors. The Product aspect showed fluctuating CDR and treatment success rates that had not yet reached the national target, and the detection of suspected TB tended to decrease. In conclusion, although regulations and commitments were in place, the program required strengthening human resources, diagnostic tools, anti-stigma socialization, cross-sectoral work, and adaptive funding support to achieve TB elimination. Keywords: CIPP, Program Evaluation, TB Control, Tuberculosis.